Chapter Solidarietà, doveri e cittadinanza europea - POLACCHINI, FRANCESCA (Studi e saggi, 2022)
Europe has been constituted as a community of rights, freedom and equality, but has so far been unable to provide an adequate cultural and regulatory elaboration of the principle of solidarity, an essential tool for the construction of a real political community, in which the European citizen is a holder of rights, but also of duties. In the context of a historical contingency in which the economic crisis and the humanitarian crisis have determinated deep and dramatic lacerations in the social tissue, recovering and relaunching the dimension of duties in a solidaristic key seems a task that can no longer be postponed. In view of the possibility of outlining a relationship of mutual implication between identity, solidarity and fiscal responsibility, the establishment of a European tax duty could represent the premise for genuine social solidarity among the citizens of a single European political entity.